Analisis dan Perancangan Sistem Informasi Pendaftaran Izin Survei dan Magang dengan Pendekatan Berorientasi Objek (Studi Kasus: Dinas Kesatuan Bangsa dan Politik, Pemerintahan Kota Batu) - Resna Yulita; Ismiarta Aknuranda; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The National Unity and Political Unit (Kesbangpol) of Batu City is a service that engages in politics to improve national security and unity in Batu City and has several external services, namely survey and apprenticeship services, mass organization registration services and information services on political development and intelligence information. In carrying out its activities this service uses a manual method for survey permit and apprenticeship registration services. Applicants (students and students) who will conduct surveys and internships in various Regional Organizations (OPD) or Dinas in Kota Batu must visit the office of the National Unity and Political Office of Kota Batu by bringing several requirements to obtain a registration permit. Constraints and problems faced are when a signature is needed from the head of office but the head of office is out of town or not in the room and the applicant who lives far from Kesbangpol Batu City is having trouble registering by visiting the office and risk losing file. To overcome these problems, a survey permit and apprenticeship permit information system is needed. System analysis and design is carried out using an object oriented approach. Evaluation in research uses consistency analysis, decision table and prototype testing. This research produces a web-based information system design that allows applicants to register via the web, the Head of Office can verify registration permits and the parties concerned can carry out their duties through the system. The results of the evaluation of the information system design show consistency between the requirements with the design and testing of the prototype that produces input for design improvement.